Sistem Informasi Geografis (SIG) Lokasi Objek Wisata Kota Pariaman Berbasis Website - Reza Sugara Amri; Sularno (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
Information is an inseparable part of life activities. Human needs are increasingly complex, encouraging people to develop the latest technologies including WebGis. Likewise with the need for information about the location of tourism objects in the city of Pariaman, West Sumatra Province. The approach method used in this study is a structured design approach. Through a structured approach, complex problems in the organization can be solved and the results of the system will be easy to maintain, flexible, more satisfying the user, have good documentation, on time, according to the development budget, can increase productivity and quality will be better . With the WebGIS Application mining center in the City of Pariaman, users are expected to be easier in getting information about the location of tourism objects in the City of Pariaman.